(untitled) (An Nawawi, 2025)
This study examines the phenomenon of increasing divorce rates in Indonesia which indicates a lack of preparation for prospective brides. The Office of Religious Affairs (KUA) has a strategic role in organizing marriage guidance programs as an effort to realize the sakinah family. The purpose of the research is to analyze the role of KUA, the material presented, and the challenges in the implementation of sakinah family orientation for prospective brides. This study uses a qualitative approach with an analytical descriptive design to gain an in-depth understanding of the phenomenon being studied. Primary data through unstructured interviews with key informants. Secondary data were obtained from laws and regulations (Marriage Law, KHI), academic literature, and institutional documents. Data analysis is carried out through data reduction (selection, organization, focusing of relevant information), data presentation (narrative forms and matrices), and drawing conclusions. The results of the study show that the KUA of Pondok Aren District plays a crucial role in preparing the bride-to-be through comprehensive premarital guidance